Buildings for early-weaned pigs - James P Murphy; Joseph P Harner (Kansas Agricultural Experiment Station Research Reports, 1995)
Buildings for early-weaned pigs present several challenges to designers and building/equipment manufacturers, but the ability to provide the optimum environmental conditions for the small pig is within the reach of today's technology.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Segregated early weaning; Buildings; Engineering